2012
DOI: 10.1016/j.ijid.2012.05.818
|View full text |Cite
|
Sign up to set email alerts
|

Cholera outbreak in village Haji Aijaz Solangi, District Naushahro Feroze, Sind, Pakistan, May 2011

Abstract: Background: On 9th May 2011 Pediatrician DHQ Naushahro Feroze reported about some patients of AWD at DHQ hospital with varying complaints of diarrhea, abdominal pain, vomiting, dehydration and fever. An investigation was carried out to identify the source and mode of spread of the disease.Methods: Data was collected from the concerned hospital and the affected village was also visited. All individuals of any age passing more than three watery stools in 24 hours from 9th May, 2011 to 20th May, 2011 were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The UV radiation in time dependent dose (0, 5, 10, 20, 40, 80 and 160 min) was used to decontaminate AF in open grains and the grains packed in sacks. The results demonstrated 80-90 % and 65-73 % respectively, decrease in the AF levels in both wheat samples exposed to the UV light (Ghanghro et al, 2016).…”
Section: Uv Light Irradiationmentioning
confidence: 80%
See 1 more Smart Citation
“…The UV radiation in time dependent dose (0, 5, 10, 20, 40, 80 and 160 min) was used to decontaminate AF in open grains and the grains packed in sacks. The results demonstrated 80-90 % and 65-73 % respectively, decrease in the AF levels in both wheat samples exposed to the UV light (Ghanghro et al, 2016).…”
Section: Uv Light Irradiationmentioning
confidence: 80%
“…The AF have been found to be very sensitive to the treatment with the UV light and the UV light was found to be the most effective method used in reduction of AF level in wheat and to protect grains from deterioration during storage (Ghanghro et al, 2016). Several studies demonstrated that the AF production could be affected by the light without damaging nutritional qualities of food (Samarajeewa et al, 1990).…”
Section: Uv Light Irradiationmentioning
confidence: 99%